GREEN ECONOMY AND GREEN GROWTH. INITIAL EFFORTS OF SUSTAINABLE DEVELOPMENT IN UZBEKSITAN - Najmiddinov, Yaxyo (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
Green economy and green growth play a key role in the transformation to the sustainable development from traditional development. In the world all nations are trying to change their traditional economy to the sustainable economic development in the form of green economy and green growth. In this paper, we have taken mostly into consideration all fields of green economy such as creating energy efficiency policies, enhancing to produce green product and increase the consumption of green products, promoting green jobs, upgrading environmental and socioeconomic impacts of the country’s latest green economy policies and green growth strategies for the upcoming years. We have tried to demonstrate profitable sides of the long term sustainable development rather than short term benefits of the new policies.